Pengaruh Material Konservasi Kolostrum terhadap Pelepasan Ion Ni - Grahita Aditya; Hikmah Nuraini; Whinahyu Aji Sekarini (Jurnal Teknosains, 2019)
Nickel in orthodontic bracket will be released immediately in the oral cavity. The release of Ni ion may trigger type IV hypersensitivity reaction. Colostrum has a high content of lactoferrin which can inhibit T cells proliferation after nickel sensitization, and decrease oxidative stress. Adding potassium sorbat 0.5%, or fermentation of colostrum may extend colostrum storage. The purpose of this research is to know the difference of nickel ion release in colostrum with 0.5% potassium sorbat addition and fermented colostrum. Methods of the study were laboratory experimental with four groups, colostrum and 0.5% potassium sorbat, fermented colostrum, sodium fluoride and artificial saliva. The sample was incubated in 40°C for 7 days. Nickel ions was measured using an inductively coupled plasma-optical emission spectrophotometry (ICP-OES Perlun Elmer Optima 8300®). Ni ions release differences were tested using the Kruskall-Wallis and Mann Whitney test.The lowest rate of Ni ion release wasfound in the colostrum group with 0.5% potassium sorbat followed by the fermented colostrum group. Kruskal-Wallis test no significant difference (p> 0,05) in each study group. The Mann Whitney test found significant differences between colostrum solution with 0.5% potassium sorbat and sodium fluoride, and also artificial saliva. The results concluded that colostrum with 0.5% potassium sorbat inhibit the release of Ni ions.